Fostering teenagers' assessment of information reliability: Effects of a classroom intervention focused on critical source dimensions. (December 2018) - Pérez, Ana; Potocki, Anna; Stadtler, Marc; Macedo-Rouet, Mônica; Paul, Johanna; Salmerón, Ladislao; Rouet, Jean-François
Abstract: Increased amounts of information available from the Internet have triggered new demands for students to evaluate information quality. Our study presents an instructional intervention aimed at fostering ninth grade students' critical evaluation of source reliability. The intervention was grounded into theories of multiple text comprehension and used an analytic framework that defines the core source dimensions of author position (competence), author motivation (intention), and media quality (pre-publication validation). Compared to controls, trained students 1) reduced the score assigned to links containing less reliable information in the three critical source dimensions (knowledge application task), as well as 2) increased the number of references made to a more reliable source (e.g., " scientific journal ") and decreased references made to a less reliable source (e.g., " personal blog "), in a task presenting contradictory information across texts (transfer task). Nonetheless, the intervention outcomes varied according to the type of source evaluation question. We discuss the beneficial effects of implementing classroom intervention on sourcing skills as a means to improve teenagers' critical thinking when comprehending multiple documents. Highlights: Teenagers experience difficulties when comprehending multiple documents. Teenagers' critical thinking can be improved by training sourcing skills. Trained students rated less reliable information sources more negatively. Trained students increased references made to more reliable source information. Intervention benefits varied according to the type of source assessment question.